Early school leaving & youth unemployment. - De Groof, Saskia, ....-; Elchardus, Mark, 1946- (Leuven : LannooCampus, 2013)
Early school leaving and youth unemployment are on top of the societal and political agendas, both in Belgium and in Europe. More and more observers fear a 'lost generation' of young people who, by the combined effects of educational failure and unemployment, see their chances for a fulfilling and productive life seriously diminished. Integrating and keeping young people into education and the labour market is becoming a huge challenge and a priority for European societies. Early school leaving & youth unemployment is the result of an international call for scientific papers by the P&V Foundation, which aimed to reward articles that succeed to elucidate in a rigorous, empirical and original way the causes of and possible solutions for early school leaving and/or youth unemployment in Belgium and other OECD societies. The authors come from different disciplines, such as sociology, economy, education and labour market studies.
Keywords: Voortijdige schoolverlaters; Jeugdwerkloosheid